2019
DOI: 10.1590/interface.180095
|View full text |Cite
|
Sign up to set email alerts
|

A cobertura jornalística sobre temas de interesse para a Saúde Coletiva brasileira: uma revisão de literatura

Abstract: É escassa a produção de revisão de literatura sobre a cobertura jornalística de temas de interesse para a Saúde Coletiva. O presente estudo teve como objetivo caracterizar o perfil da produção científica, publicada de 2000 a 2015, voltada para a análise de notícias que tratam de temas da saúde das populações. Os 64 manuscritos incluídos foram organizados nas seguintes categorias: tema, produção de dados, métodos de análise e meios de comunicação investigados. A temática predominante foi a cobertura midiática s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
3
0
2
Order By: Relevance
“…Despite the meaningful number of studies previously selected to compose this review, few studies have been identified that have focused on mental disorders in the context of incarceration. A study developed by Langbecker et al (28) highlighted that the journalistic interest on this theme in collective science in Brazil is minimal, when compared to the high prevalence of these disorders in the Brazilian population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the meaningful number of studies previously selected to compose this review, few studies have been identified that have focused on mental disorders in the context of incarceration. A study developed by Langbecker et al (28) highlighted that the journalistic interest on this theme in collective science in Brazil is minimal, when compared to the high prevalence of these disorders in the Brazilian population.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that most studies have highlighted the speech of health professionals, to the detriment of people with mental disorders in conflict with the Law and their families. The research conducted by Lanbecker et al (28) points this out, in which the voice of people with schizophrenia is invisible in the setting of health research in Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(impressos e digitais) contam com espaços destinados ao tema, o que pode facilitar a ampliação da discussão (15) . Os meios de comunicação podem ser classificados a partir de três sistemas ou gêneros comunicacionais:…”
Section: Comprovadamente Muitos Idososunclassified
“…Nos estudos investigados, houve a predominância da análise da mídia impressa. Esses achados são similares aos de Catalan-Matamoros & Peñafiel-Saiz, (2017), Terrón et al, (2017) e Langbecker et al (2019), não sendo objeto de estudos programas de rádio e sites de notícias. Somente um artigo investigou programas de televisão.…”
Section: )unclassified